2024
DOI: 10.32890/mjli2024.21.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Project-Based Learning and Projectbased Flipped Classroom on Critical Thinking and Creativity for Business English Course at Higher Vocational Colleges

Lijie Hao,
Kun Tian,
Umi Kalsum Mohd Salleh
et al.

Abstract: Purpose – With the evolving demands of the global and Chinese economies, cultivating critical thinking and creativity has become imperative for social and economic development. However, contemporary educational practices have not kept pace with thisessential need. This study examines the effects of project-based learning and project-based flipped classrooms on critical thinking and creativity in higher vocational colleges. Moreover, this research delves into the disparity and comparative analysis between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In contemporary educational discourse, the advent of online learning platforms has transformed the teaching and learning landscape, offering unprecedented opportunities for access, flexibility, and innovation (Hao et al, 2024;Mielikäinen & Viippola, 2023;Plews et al, 2024). Concurrently, educators have been exploring diverse pedagogical approaches to optimize the online learning experience, among which Project-Based Learning (PjBL) has emerged as a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contemporary educational discourse, the advent of online learning platforms has transformed the teaching and learning landscape, offering unprecedented opportunities for access, flexibility, and innovation (Hao et al, 2024;Mielikäinen & Viippola, 2023;Plews et al, 2024). Concurrently, educators have been exploring diverse pedagogical approaches to optimize the online learning experience, among which Project-Based Learning (PjBL) has emerged as a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Collaboration: Collaborative inquiry and teamwork are central to PjBL, enabling students to leverage diverse perspectives, skills, and resources to achieve shared goals (Lyu et al, 2023;Zhang et al, 2024). c. Inquiry: PjBL encourages inquiry-driven exploration, where students pose questions, conduct research, and generate solutions through self-directed investigation (Guo et al, 2022;Plews et al, 2024) d. Reflection: Reflective practices promote metacognition and deep understanding by encouraging students to critically evaluate their learning processes, outcomes, and areas for growth (do Amaral et al, 2023;Hao et al, 2024). This study proposes a comprehensive investigation into students' experiences with Project-Based Learning in online educational contexts to address this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Rooted in constructivist learning theories, PjBL shifts the focus from traditional teacher-led instruction to student-centered inquiry and collaboration, where students engage in authentic, real-world projects to construct knowledge and solve complex problems Singgih Subiyantoro / Exploring Teachers' Perspectives on their Role in Facilitating Project-Based Learning: A Comparative Study of Elementary, Middle, and High School (Chang et al, 2024;Melia Astiana, Maya Malinda, Anny Nurbasari, 2021;Şahin & Kılıç, 2024). Over the years, PjBL has garnered attention from educators, researchers, and policymakers for its potential to promote critical thinking, creativity, communication, and collaboration skills, which are essential for success in the modern workforce (Hao et al, 2024;Şahin & Kılıç, 2024;Wijnia et al, 2024). Despite the growing interest and adoption of PjBL in educational practice, there remains a gap in understanding the intricate role of teachers in facilitating this instructional approach.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chang et al (Chang et al, 2024) conducted a longitudinal study in higher education classrooms and found that students engaged in PjBL projects demonstrated higher levels of conceptual understanding and problem-solving skills than those in traditional classrooms. Hao et al (Hao et al, 2024), do Amaral et al (do Amaral et al, 2023), and Ismail et al (2024 examined PjBL studies and concluded that PjBL positively impacts student achievement, motivation, and 21st-century skills. While research on PjBL has primarily focused on student outcomes, there is a growing interest in understanding teachers' perspectives on their role in facilitating PjBL.…”
Section: Introductionmentioning
confidence: 99%